2018
DOI: 10.1007/s00439-018-1888-x
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced maternal parent-of-origin bias for type-1 NF1 microdeletions

Abstract: Neurofibromatosis type 1 (NF1) is caused, in 4.7-11% of cases, by large deletions encompassing the NF1 gene and its flanking regions within 17q11.2. Different types of large NF1 deletion occur which are distinguishable by their breakpoint location and underlying mutational mechanism. Most common are the type-1 NF1 deletions of 1.4 Mb which exhibit recurrent breakpoints caused by nonallelic homologous recombination (NAHR), also termed unequal crossover. Here, we analyzed 37 unrelated families of patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…We conclude that NAHR is the preponderant mutational mechanism causing type-1 NF1 deletions. Previous analyses have indicated that the majority of type-1 NF1 deletions are of maternal origin and caused by an interchromosomal exchange during meiosis I (López-Correa et al, 2000;Neuhäusler et al, 2018). Taken together with the data presented here, we may infer that NAHR during meiosis is the predominant mechanism underlying type-1 NF1 deletions.…”
Section: Discussionsupporting
confidence: 78%
“…We conclude that NAHR is the preponderant mutational mechanism causing type-1 NF1 deletions. Previous analyses have indicated that the majority of type-1 NF1 deletions are of maternal origin and caused by an interchromosomal exchange during meiosis I (López-Correa et al, 2000;Neuhäusler et al, 2018). Taken together with the data presented here, we may infer that NAHR during meiosis is the predominant mechanism underlying type-1 NF1 deletions.…”
Section: Discussionsupporting
confidence: 78%
“…We identified parent-of-origin studies that met the following criteria: (1) the study detailed parent of origin data for NAHR-mediated loci as designated by Coe et al, 2014 15 , (2) the study reported parent of origin data for non-imprinted loci, (3) the study reported data for more than 10 families with affected children, and (4) the study clearly treated monozygotic twins as one meiosis event. 25 studies met inclusion criteria; from these 25 studies, data were curated for six loci, including copy number variants at 5q35.3 9,36 , 7q11.23 1,7,37-42 , 16p11.2 5 , 17p11.2 [43][44][45] , 17q11.2 8,31,32 , and 22q11.2 6,38,[46][47][48][49][50][51] (Table 1). Each locus has between one and eight independent studies representing in total 1,438 de novo deletion and duplication events.…”
Section: Recurrent Genomic Disorder Loci Literature Searchmentioning
confidence: 99%
“…Parental bias for the origin of recurrent de novo CNVs remains unexplained. De novo deletions at the 16p11.2 and 17q11.2 loci are more likely to arise on maternally inherited chromosomes 5,8,31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…We curated studies that reported parental origin of CNV (deletions and duplications) at these loci using a systematic PubMed search and the following set of inclusion criteria: 1) the study detailed parent of origin data within one of the NAHR-mediated loci as designated by Coe et al, 2014 [8], (2) the study reported parent of origin data for non-imprinted loci, (3) data were reported for more than 10 families with affected children, and (4) the study clearly treated monozygotic twins as one meiosis event (Additional File 1: Supplemental Methods and Additional File 2: Table S1). We identi ed six loci for further analysis: 5q35.3 [31,32], 7q11.23 [24,[36][37][38][39][40][41][42], 16p11.2 [26], 17p11.2 [43][44][45], 17q11.2 [27][28][29], 22q11.2 [30,37,[46][47][48][49][50][51]. At a seventh locus (3q29) we generated new data to determine the parent of origin for de novo events.…”
Section: Parent Of Origin Determination Literature Search and Data Cumentioning
confidence: 99%
“…Parental bias for the origin of recurrent de novo CNVs remains unexplained. De novo deletions at the 16p11.2 and 17q11.2 loci are more likely to arise on maternally inherited chromosomes [26][27][28][29]. Deletions at the 22q11.2 locus show a slight maternal bias as well [30].…”
Section: Introductionmentioning
confidence: 99%